Comparison of antibiotic prescribing in 2001 and 2007: A study from the portuguese Sentinel Network of Family Doctors (Portuguese Journal of Family Medicine and General Practice, 2012)
COMPARISON OF ANTIBIOTIC PRESCRIBING IN 2001 AND 2007: A STUDY FROM THE PORTUGUESE SENTINEL NETWORK OF GENERAL PRACTITIONERSObjectives: To compare the prescription of cephalosporins and quinolones by general practitioners in the Sentinel Network in2007, with the results of a similar study conducted in 2001, determining: the number of antibiotics (AB) prescribed per 1.000 patients and, of all AB prescribed, the proportion of prescriptions of cephalosporines and quinolones.Design: cross-sectional.Setting: Portuguese Health Centers belonging to the Portuguese Sentinel Practice NetworkPopulation: Patients registered on the lists of general practitioners belonging to the Sentinel NetworkMethods: This study was conducted within the Portuguese Sentinel Network of General Practitioners, allowing for population based estimates to be obtained because the composition of the patient list of the participating physicians is known from the outset. AB prescribing was reported from 2001 and 2007. Annual prescription rates (nANTI = number of prescriptions of an- tibiotics per 1.000 individuals) by sex and age were calculated.Results: In 2001, 12.184 prescriptions were studied and in 2007, 9.034 prescriptions for AB were studied. In 2007 the rate of prescription of cephalosporins was 8,2 per 1.000 individuals and the proportion was 10.1% the total of AB prescribed. This was lower than in 2001 when the nANTI was 11,1 and the proportion was 11,9%. The rate of prescription of quinolones was lower in 2007 (nANTI = 13,2) than in 2001 (nANTI = 14,2), but the proportion of quinolones among all AB prescriptions was higher in 2007 (16,2%) than in 2001 (15,3%).Conclusions: The rate of prescribing of cephalosporins and quinolones per 1.000 individuals was lower in 2007 compared to2001. The proportion in the total of AB prescribed was lower for cephalosporins, but higher for quinolones in 2007. Among pa- tients aged 75 years and older the proportion increased in 2007, for both classes (cefalosporines and quinolones), but the in- crease was statistically significant for quinolones only.
Keywords: Prescriptions; Therapeutics; Anti-Bacterial Agents; Family Physicians; Sentinel Network of General Practitioners